(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
In two vineyards, variety "Rodhitis," located in the territories of Mesinikola near Karditsa and Nea Anhialos near Volos, have been carried out field trials to check collateral effects of six commercial preparations of microbial insecticide Bt, (Agree WP, Bactecin D, Bactospeine WP, BPM 123 WP, Dipel 8L WP and Xen-Tari WG), two formulations of synthetic pyrethroid deltamethrin and two fungicides folpet and copper hydroxide (Kocide 101WP) on Phytoseius finitimus (Ribaga), during the years 2000-2002. The products were sprayed in the vineyard areas only, at the time recommended for the control of the grape moth and downy mildew respectively. The two formulations of the pyrethroid deltamethrin Decis EC and Decis WG (new formulation) were found high toxic (mortality 100% on juveniles and adults of Ph. finitimus) a week after application and its persistence lasted about for one month after spraying. The Bt preparations (Agree WP, Bactecin D, Bactospeine WP, BPM 123 WP, Dipel 8L WP and Xen-Tari WG), appeared to be harmless one week after the first application. Ten days after the second application Agree WP, BPM 123 WP and Bactecin D showed slightly toxic, while Dipel 8L WP was moderately toxic (52.2%). However, twenty one days after the second application all the compounds were harmless afterwards: On the other hand, folpet and copper hydroxide were completely harmless’ on Ph. finitimus. These two fungicides and the Bt compounds may be used in integrated control programs of and only the effect of Dipel 8L WP depends on its frequency of application.